2019
DOI: 10.1002/ccd.28536
|View full text |Cite
|
Sign up to set email alerts
|

Three‐year clinical outcome in all‐comers with “silent” diabetes, prediabetes, or normoglycemia, treated with contemporary coronary drug‐eluting stents: From the BIO‐RESORT Silent Diabetes study

Abstract: Background: Patients with coronary disease may have unknown diabetes or prediabetes. We evaluated 3-year outcomes after percutaneous coronary intervention (PCI) with contemporary drug-eluting stents (DES) in patients with silent diabetes, prediabetes, and normoglycemia. Methods: All BIO-RESORT trial (NCT01674803) participants without known diabetes, enrolled at our center, were invited for oral glucose tolerance testing (OGTT) and measurements of fasting plasma glucose and glycated hemoglobin (HbA1c). Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…A previous subgroup analysis of BIO-RESORT assessed 324 patients with prediabetes, 793 with diabetes, and 1869 with normoglycemia and showed that patients with prediabetes, similar to patients with diabetes, had higher 1-year risks of mortality and repeat revascularization after treatment with contemporary DES [ 4 ]. Furthermore, the BIO-RESORT Silent Diabetes study [ 24 ] previously reported that patients with prediabetes and silent diabetes—assessed by oral glucose tolerance testing and HbA1c at the time of the index procedure—had a higher 3-year risk of TVF. Yet, this was mainly driven by events during the first 48 h. Those previously reported data and the findings of the present study suggest that patients with prediabetes have an increased risk of ischemic events.…”
Section: Discussionmentioning
confidence: 99%
“…A previous subgroup analysis of BIO-RESORT assessed 324 patients with prediabetes, 793 with diabetes, and 1869 with normoglycemia and showed that patients with prediabetes, similar to patients with diabetes, had higher 1-year risks of mortality and repeat revascularization after treatment with contemporary DES [ 4 ]. Furthermore, the BIO-RESORT Silent Diabetes study [ 24 ] previously reported that patients with prediabetes and silent diabetes—assessed by oral glucose tolerance testing and HbA1c at the time of the index procedure—had a higher 3-year risk of TVF. Yet, this was mainly driven by events during the first 48 h. Those previously reported data and the findings of the present study suggest that patients with prediabetes have an increased risk of ischemic events.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with pre-DM can suffer from CHD even before progressing to overt diabetes [20]. The recent BIO-RESORT Silent Diabetes study [21], which enrolled a cohort of acute and chronic CHD patients categorized as silent DM, pre-DM, and normoglycemia, showed that 3 years after PCI with contemporary DES, pre-DM patients had higher rates of adverse clinical events than patients with normoglycemia. However, a landmark analysis revealed that the aforementioned differences in clinical endpoints at 3-year follow-up were mainly based on events that had occurred during the first 48 h, driven by a higher rate of periprocedural MI [21].…”
Section: Discussionmentioning
confidence: 99%
“…The recent BIO-RESORT Silent Diabetes study [21], which enrolled a cohort of acute and chronic CHD patients categorized as silent DM, pre-DM, and normoglycemia, showed that 3 years after PCI with contemporary DES, pre-DM patients had higher rates of adverse clinical events than patients with normoglycemia. However, a landmark analysis revealed that the aforementioned differences in clinical endpoints at 3-year follow-up were mainly based on events that had occurred during the first 48 h, driven by a higher rate of periprocedural MI [21]. In line with these and our results, the ARTEMIS (Innovation to Reduce Cardiovascular Complications of Diabetes at the Intersection) study concluded that the risk of cardiac events does not differ between patients with CHD plus pre-DM who have undergone revascularization or OMT and those with normal glycemic status [5].…”
Section: Discussionmentioning
confidence: 99%
“…Xia et al reported that high GV correlated with an increased incidence of troponin release after PCI [72]. More recently, patients with an abnormal glucose metabolism detected by oral glucose tolerance testing documented a higher incidence of myocardial infarction and cardiac death within 48 h after PCI [73].…”
Section: Preprocedural Myocardial Injurymentioning
confidence: 99%